2000
DOI: 10.1086/313929
|View full text |Cite
|
Sign up to set email alerts
|

Human Parvovirus B19 Infection in Infancy Associated with Acute and Chronic Lymphocytic Myocarditis and High Cytokine Levels: Report of 3 Cases and Review

Abstract: Human parvovirus B19 infection is occasionally associated with acute lymphocytic myocarditis (ALM). Three infants with B19 virus-associated ALM were followed up clinically, histologically, and immunovirologically. Each infant had B19 virus DNA in the blood or B19 virus-specific IgM antibodies. Two infants with postnatal infection recovered after immunosuppressive therapy. The third infant with possible prenatal infection developed chronic persistent myocarditis associated with persistent B19 virus DNA in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 35 publications
2
71
0
Order By: Relevance
“…The large number of endothelial cells in the close-meshed capillary and venular network of the human heart provides a reservoir for persistent as well as latent virus infection. The possible persistence of B19 infection has been demonstrated recently by the analyses of consecutive endomyocardial biopsy specimens of patients with progressive systolic left ventricle dysfunction (45,59). With regard to the restricted B19 replication in endothelial cells, we have strong evidence that B19 RNA synthesis does occur in cardiac endothelium during acute myocarditis.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The large number of endothelial cells in the close-meshed capillary and venular network of the human heart provides a reservoir for persistent as well as latent virus infection. The possible persistence of B19 infection has been demonstrated recently by the analyses of consecutive endomyocardial biopsy specimens of patients with progressive systolic left ventricle dysfunction (45,59). With regard to the restricted B19 replication in endothelial cells, we have strong evidence that B19 RNA synthesis does occur in cardiac endothelium during acute myocarditis.…”
Section: Discussionsupporting
confidence: 51%
“…Several studies disclosed an association between B19 and a variety of diseases (43,48,63,80), such as arthritis (56, 77), vasculitic syndromes (19, 24, 31, 80), hepatitis (27,36,38,75,85), and neurological disorders (2, 85). Specifically, B19 infections have been observed to be associated with acute and chronic myocarditis (13,16,30,44,53,(58)(59)(60)71). Moreover, the development of endothelial and isolated left ventricle diastolic dysfunction has been associated with B19 infection (81).…”
mentioning
confidence: 99%
“…46 In our study, we demonstrated that TNFa was significantly more expressed in viral myocarditis than in nonviral forms (16/20 vs 3/18, P ¼ 0.01), regardless of the viral etiology: capside or viral proteins have been demonstrated to be responsible for the attraction mainly of Th1 cells with consequently over-release of specific proinflammatory cytokines, just including TNFa.…”
Section: Tnfa and Tnfa Receptors In Human Myocarditismentioning
confidence: 50%
“…B19 viremia usually reaches a peak at days 7-9 after infection and is resolved by the development of an IgM-and IgG-antibody response starting a few days later. Despite the development and presence of B19-specific immune reactions, ϳ20% of all B19 infections show a prolonged state of viremia or viral persistence restricted to the synovial fluid, and viral genomes are detected in bone marrow or other organs, e.g., synovial tissue, liver, or myocardium, for several years after infection (4,8,12,13,19,27,(29)(30)(31)(32)(33). Compared with our age-matched control group and compared with healthy adult blood donors, who have been shown to contain B19 DNA in 7% and in 0.1% up to 0.6% of cases, respectively (34)(35)(36), viral genomes were detected in 35% of arthritis patients in the present study.…”
Section: Discussionmentioning
confidence: 99%